(untitled) (Journal of Parents and Teachers, 2023)
The different situations that we live day by day can generate nerves and tension, giving rise to the appearance of the "temper". This can lead us to have wrong and hasty reactions, so we should consider methods to control it. Therefore, we analyze the ways in which it can appear (internally or externally) and some techniques to control it, such as self-observation or visualization.